Increasing Financial Literacy With “Moma” Money Management Learning Media In Vocational High Schools: Meningkatkan Literasi Keuangan Dengan Media Pembelajaran “Moma” Money Management Di Sekolah Menengah Kejuruan - Saputri, Agatha; Nurrahman, Arief; Zylio Nugraha, R. Andro; Rosyad Achmadi, Caesar; Harfiansyah Makarim, Muhammad; Murti Sagoro, Endra (Jurnal Pendidikan Akuntansi Indonesia, 2025)
Financial literacy is one of the essential life skills that must be possessed by every individual, especially vocational students. However, financial learning media used in schools tend to be conventional and not interactive. Therefore, innovation is needed in the form of interactive learning media that can present relevant, interesting, and applicable learning experiences. This research is development research (R&D) that aims to improve the financial literacy of Vocational High School students through the development of "MOMA" Money Management learning media. The product feasibility test was conducted by material experts, media experts, teachers, and students. Data collection was done through interviews and questionnaires. The data collection instruments used were interview guidelines, expert validation questionnaires, teacher response questionnaires, and student response questionnaires. The feasibility of the learning media produced was analysed using the conversion of 5 quantitative categories. The result of this research is an android game-based learning media "MOMA" Money Management in learning financial literacy Vocational High School. The learning media “MOMA” is proven to be effective in improving students' understanding of the basic concepts of financial management. The learning media is considered feasible by material experts, media experts, teachers, and students. This media is also adaptive and easily accessible.